THE ROLE OF DIETARY SUPPLEMENTS IN INFLAMMATORY BOWEL DISEASE : A SYSTEMATIC REVIEW - Hardiyansah, M. Yudhi; Azhari, Ririn; Yulanda Putra, Yosie; Syarfina, Afdila; Merisa L, Bella (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: The microbiome is an important contributor to a variety of fundamental aspects of human health, including host metabolism, infection, and the immune response. Gut dysbiosis has been inditified as a contributor to the errant immune response in disease such as inflammatory bowel disease. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 58 articles, whereas the results of our search on SagePub brought up 177 articles. The results of the search conducted for the last year of 2013 yielded a total 39 articles for PubMed and 9 articles for SagePub. In the end, we compiled a total of  5 papers, 4 of which came from PubMed and 1 of which came from SagePub. We included five research that met the criteria. Conclusion: In summary, most substances reviewed showed a positive effect on patients with IBD and their clinical symptoms. Fibers have also shown similar results. Those fibers, such as fructans, psyllium, oat bran, and barley foodstuff have relieved some gastrointestinal symptoms that have been associated with IBD, this has improved patient’s quality of life. The fatty acids reviewed have proved to be effective in decreasing corticosteroid use among may IBD patients. Probiotics have shown some promising results; however, more testing is required to provide definite results. Lastly, low FODMAP diets have also shown a very positive effect in decreasing uncomfortable gastrointestinal symptoms.